1998
DOI: 10.1046/j.1365-2567.1998.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functions of interferon‐γ for chemokine expression in models of acute lung inflammation

Abstract: Challenge of the immune system with bacterial superantigens or endotoxin induces the systemic release of cytokines followed by lethal septic shock. The lung is particularly susceptible to systemic toxin exposure resulting in acute leucocyte infiltration and vascular damage. In the present study, the functions of interferon-gamma (IFN-gamma) and tumour necrosis factor (TNF) for chemokine regulation during acute lung inflammation were examined. Following administration of the superantigen, staphylococcal enterot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…While no studies correlating S. aureus pneumonia and MCP-1 have been performed in mice, this has been examined in a number of related models. Pulmonary MCP-1 is increased following administration of the superantigen staphylococcal enterotoxin B; however, this is unrelated to IFN-γ, since MCP-1 levels are similar in control and IFN-γ-knockout mice (34). Pseudomonas aeruginosa pneumonia increases MCP-1 levels, associated with increased numbers of alveolar macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…While no studies correlating S. aureus pneumonia and MCP-1 have been performed in mice, this has been examined in a number of related models. Pulmonary MCP-1 is increased following administration of the superantigen staphylococcal enterotoxin B; however, this is unrelated to IFN-γ, since MCP-1 levels are similar in control and IFN-γ-knockout mice (34). Pseudomonas aeruginosa pneumonia increases MCP-1 levels, associated with increased numbers of alveolar macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…At an early time point of renal IRI, we demonstrated an increase in the influx of CD4 ϩ T cells and NKT cells. Chemokines mediate leukocyte migration into the injured kidney and IFN-␥ modulates chemokine production, including IFN-␥-inducing protein 10 (IP-10), monokine-induced by IFN-␥, and IFN-␥-inducible T cell chemoattractant production, which bind to CXCR3 to mediate T cell migration (25) (25)(26)(27)(28)(29)(30). Our previous study showed that renal IRI up-regulated IP-10 and MIP␣, MIP1␤, MIP2, which are thought to mediate T cell and neutrophil migration (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some CKs such as LIX and MIP-2 were induced independently of TNF-␣ as was previously reported in TNF receptor knockout mice stimulated with superantigens. 74 It should be noted that because of the great effort required to monitor numerous CKs in multiple samples we focused analysis on the rapid recruitment period, day 2. Further studies will be needed to determine whether later stage CKs are influenced by cytokine depletions.…”
Section: Discussionmentioning
confidence: 99%